Influence of pain on postural control in women with neck pain - Juliana Soares; Priscila Weber; Maria Elaine Trevisan; Claudia Trevisan; Carlos Bolli Mota; Angela Garcia Rossi (Universidade Federal de Santa Catarina, 2013)
The objective of this study was to investigate the influence of pain on postural control in women with neck pain and the relationship with possible changes in sensory systems and posture. The neck pain group was composed of women, aged between 20 and 50years, complaining of neck pain for more than three months; the control group was composed of women without complaints of neck pain. For the characterization of the groups, we used anamnesis, neck disability index and Visual Analogue Scale. Postural balance was assessed on force platform. Postural balance with manipulation of the sensory systems was measured by Foam Laser Dynamic Posturography, exposing the individual to six sensory organization tests. Posture was assessed by the Postural Assessment Software. The normality of the variables were verified using Shapiro-Wilk test, Student's t-test and Mann-Whitney test for comparison between groups, with a significance level of5%. Groups were homogeneous in demographic variables. We observed higher amplitude and displacement velocity of the center of pressure in the neck pain group, showing greater postural balance. There were significant diferences incraniovertebral angle, showing forward head posture in symptomatic women. In dynamics posturography, we observed a difference between the groups: the score obtainedin the six sensory conditions showed that neck pain group presented greater balance impairment. Neck pain and forward head posture have a deleterious effect on postural control in symptomatic women, both in the static posture and dynamic posture.